Will You Accept an Imperfect AI? Exploring Designs for Adjusting End-user Expectations of AI Systems - Kocielnik, Rafal; Amershi, Saleema; Bennett, Paul (CHI 2019, 2019)
AI technologies have been incorporated into many end-user applications. However, expectations of the capabilities of such systems vary among people. Furthermore, bloated expectations have been identified as negatively affecting perception and acceptance of such systems. Although the intelligibility of ML algorithms has been well studied, there has been little work on methods for setting appropriate expectations before the initial use of an AI-based system. In this work, we use a Scheduling Assistant-an AI system for automated meeting request detection in free-text email - to study the impact of several methods of expectation setting. We explore two versions of this system with the same 50% level of accuracy of the AI component but each designed with a different focus on the types of errors to avoid (avoiding False Positives vs. False Negatives). We show that such different focus can lead to vastly different subjective perceptions of accuracy and acceptance. Further, we design expectation adjustment techniques that prepare users for AI imperfections and result in a significant increase in acceptance.